Studi Kajian Tingkat Kemiskinan di Kota Medan - Devani Pratiwi; Sisiliana; Edy Suprayetno; Ulfah Setia Iswara; Dewi Mahrani Rangkuty (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine the level of poverty in the Medan city area and how the government's efforts or solutions in handling it. A descriptive qualitative study with a literature method through literature studies from journals of previous research results related to poverty-level studies. The data used in this study is secondary data obtained from the Central Bureau of Statistics of Medan City. The study results explain that Medan City has always tried to overcome the problem of poverty to the maximum; in fact, poverty is still a severe problem. Overcoming poverty requires integrating various development policies and programs in multiple sectors. The best way to fight poverty is to promote policies strengthening economic messages and positions. The driving factor of poverty in Medan City is uneven development.